2022
DOI: 10.1002/lipd.12336
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid analysis and isotopic enrichment is suggestive of greater lipogenesis in young long‐term cannabis users: A secondary analysis of a case–control study

Abstract: Cannabis is now legal in many countries and while numerous studies have reported on its impact on cognition and appetite regulation, none have examined fatty acid metabolism in young cannabis users. We conducted an exploratory analysis to evaluate cannabis impact on fatty acid metabolism in cannabis users (n = 21) and non‐cannabis users (n = 16). Serum levels of some saturated and monounsaturated fatty acids, including palmitic, palmitoleic, and oleic acids were higher in cannabis users compared to nonusers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…It has been speculated that cannabis users may have increased metabolic rates, but this data are purely speculative, and we observed no indication of this in this study (Clark et al., 2018 ). Another secondary analysis of a larger trial reported higher levels of palmitic, palmitoleic, and oleic acids in the serum of cannabis users compared to nonusers; in addition, the authors estimated de novo lipogenesis (DNL) from the ratio of palmitic acid to linoleic acid and reported higher DNL levels in cannabis users (Cisbani et al., 2022 ). The authors speculated that elevated serum glucose could have influenced palmitic acid production, though there was no difference between cannabis users and nonusers (Cisbani et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been speculated that cannabis users may have increased metabolic rates, but this data are purely speculative, and we observed no indication of this in this study (Clark et al., 2018 ). Another secondary analysis of a larger trial reported higher levels of palmitic, palmitoleic, and oleic acids in the serum of cannabis users compared to nonusers; in addition, the authors estimated de novo lipogenesis (DNL) from the ratio of palmitic acid to linoleic acid and reported higher DNL levels in cannabis users (Cisbani et al., 2022 ). The authors speculated that elevated serum glucose could have influenced palmitic acid production, though there was no difference between cannabis users and nonusers (Cisbani et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another secondary analysis of a larger trial reported higher levels of palmitic, palmitoleic, and oleic acids in the serum of cannabis users compared to nonusers; in addition, the authors estimated de novo lipogenesis (DNL) from the ratio of palmitic acid to linoleic acid and reported higher DNL levels in cannabis users (Cisbani et al., 2022 ). The authors speculated that elevated serum glucose could have influenced palmitic acid production, though there was no difference between cannabis users and nonusers (Cisbani et al., 2022 ). Furthermore, pyruvate and lactate—the end products of glycolysis—were downregulated, which suggests the possibility that they were more rapidly converted into palmitic acid in cannabis users (Cisbani et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already, we have shown sex differences in endolipids in plasma of patients with gastroparesis 22 . Likewise, serum collected from cannabis users shows increased palmitic acid, oleic acid, 2-AG, and PEA, but not AEA or OEA compared to non-cannabis users 23 , which illustrates that plasma endolipids are responsive to changes in systemic CB pharmacology. It will be informative to compare plasma levels of endolipids with CB treatments to other tissues in order to determine how translatable these values are to other parts of the body.…”
Section: Introductionmentioning
confidence: 90%
“…The method requires a very small volume of plasma (50 μL) and has a detection limit of 0.1 ng/mL. The relationships between fatty acid imbalances and the investigated diseases [44], or the influence of the use of drugs [49] have been recently reviewed.…”
Section: Gc Analysis Of Biotics In Biological Fluidsmentioning
confidence: 99%